HUBUNGAN WORKSTATION DAN POSTUR KERJA TERHADAP KELUHAN MUSCULOSKELETAL DISORDERS PADA KARYAWAN PT XYZ BEKASI TAHUN 2023 - Syafiqa Rohalia (2023)
Musculoskeletal Disorders (MSDs) was influenced by various factors such as work posture and workstations. The high workload at XYZ LLC caused white collar workers had to sit in a static position for a quite long time. This research aims to identify the association between MSDs with workstations, work posture, age, body mass index (BMI), length of work, sex, and length of sitting. The populations of this research were white collar workers on XYZ LLC with 89 sampels participated and selected by accidental sampling. This research used cross-sectional design and chi-square test for analyzed the primary data. The results showed that factors associated to MSDs were work posture (p-value = 0.007) and workstation (p-value = 0.001). Meanwhile, age (p-value = 1,000), BMI (p-value = 1.000), length of service (p-value = 0.485), sex (p-value = 1.000), and length of sitting (p-value = 0.522) has no association with MSDs. Therefore, workers must apply proper posture and stretch while work. Futhermore, the company can provide adjustable workstations and provide counseling program regarding good work posture.